Operational performance and environmental satisfaction survey of a university building with large learning commons - Yuma Tokuwaki; Takeru Kamide; Satoshi Hirakawa; Jun Maruyama; Kyosuke Hiyama (Journal of Asian Architecture and Building Engineering)
Learning Commons is being actively implemented in the design of university buildings to encourage diverse learning. Because the usage patterns of Learning Commons are different from those of regular classrooms, this design trend also has a significant impact on energy use trends in university buildings. To identify this trend, a one-year energy monitoring was conducted in a university building with a large Learning Commons built in 2022. To adjusted primary energy consumption was 599 MJ/m2year. This is a 55% reduction compared to the baseline, achieving ZEB Ready in the Japan’s definition. To analyze the students’ expectations and impressions of the building, an environmental satisfaction survey was conducted as well. From the questionnaire survey, more than 90% of the students were satisfied with the overall environment, confirming the students’ satisfaction with the building. It was also found that the satisfaction with space environment based on the space size and fixtures has a significant impact on workspace productivity related to study efficiency, as well as overall satisfaction.